Current collector and energy storage device

The use of a polymer film with conductive fillers and thin metal layers in lithium-ion battery current collectors addresses the limitations of traditional metal foils, resulting in improved battery performance and efficiency.

JP2025063011APending Publication Date: 2025-04-15DUPONT ELECTRONICS INC +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024171913
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-03
Filing Date
2024-10-01
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Current metal foils used in lithium-ion batteries are inadequate for thinner, lighter devices due to their thickness and weight, and polymer-based current collectors face challenges with thermal reliability and adhesion issues.

Method used

A current collector comprising a polymer film with a conductive filler and two thin metal layers, each 3 μm or less in thickness, which reduces the discharge voltage by at least 20% compared to untreated copper foil.

Benefits of technology

The proposed current collector achieves a lower discharge voltage, enhancing the performance and efficiency of lithium-ion batteries while addressing the challenges of thickness and weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063011000001
    Figure 2025063011000001
  • Figure 2025063011000002
    Figure 2025063011000002
Patent Text Reader

Abstract

To provide a current collector and an energy storage device.SOLUTION: In a first aspect, a current collector includes a polymer film, a first metal layer adhered to the polymer film, and a second metal layer adhered to the polymer film on a side opposite the first metal layer. The polymer film includes an electrically conductive filler and has a surface resistivity of 1 megaohm / square or less. The first and second metal layers each have a thickness of 3 μm or less. The current collector has a mid-discharge voltage that is at least 20% lower when compared to an untreated battery-grade copper foil, based on a standard lithium-ion battery half-cell test at a temperature of 25°C and a discharge rate of 2 C or greater.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The field of the disclosure is current collectors and energy storage devices. [Background technology]

[0002] Copper foil is commonly used as an anode current collector for energy storage devices such as lithium-ion batteries (LIBs) due to its high electrical conductivity, excellent chemical stability, and electrochemical stability at low potentials. A lithium-ion battery cell includes a positive electrode, a negative electrode, and a separator between the two electrodes. A conventional lithium-ion cell also includes a current collector, typically constructed from foil or mesh or metallized plastic, where the metal is composed of aluminum (for the cathode) and copper (for the anode). The cathode material is coated onto the cathode current collector (such as aluminum foil), and the anode material is coated onto the anode current collector (such as copper foil). The separator, located between the electrode layers, is typically made from a porous plastic material, and an ionically conductive organic solvent is used as the electrolyte to saturate the other components, thereby providing a mechanism for ions to conduct between the anode and cathode. These layers are typically rolled together and canned or stacked. The continuing desire for thinner and lighter devices presents challenges for the continued use of metal foils in these applications.

[0003] Polymer-based current collectors, such as metal clad laminates, can be used as an alternative to metal foils. Metal clad laminates, such as copper clad laminates, are used in electronic devices for flexible circuits as well as various electronic components for circuit packaging. Polyimide film-based copper clad laminates are typically made by either lamination for metal thicknesses greater than 5 μm or sputtering for metal thicknesses less than 5 μm. Plating (e.g., electrochemical plating and electroless plating) is an alternative method of producing laminates that has received some attention, but it has not been used much to produce laminates with copper thicknesses less than 5 μm. In addition, it is generally accepted that the reliability of plated polyimide copper laminates is below customer standards for electronic devices, making them poor candidates for use as current collectors.

[0004] Metal clad laminates produced by plating have traditionally had poor thermal reliability relative to metallization produced by sputtering or lamination of copper foil. The most reliable plated laminates use an electroless nickel seed layer. Adhesion between plated copper and polyimide films is difficult due to the presence of volatiles in the film, degradation of the film surface due to plating chemistry, and the use of film materials that do not have the functional groups for strong chemical bonding to copper, among other factors. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] US Patent Application Publication No. 2016 / 0087307A1 [Patent Document 2] U.S. Pat. No. 5,738,957 [Patent Document 3] U.S. Patent No. 8,518,525 [Non-patent literature]

[0006] [Non-Patent Document 1] Liu et al.(J.Phys.Chem.C13:15073-15079,2009) Summary of the Invention [Means for solving the problem]

[0007] In a first embodiment, the current collector includes a polymer film, a first metal layer adhered to the polymer film, and a second metal layer adhered to the polymer film opposite the first metal layer. The polymer film includes a conductive filler and has a surface resistivity of 1 Megaohm / square or less. The first and second metal layers each have a thickness of 3 μm or less. The current collector has at least a 20% lower mid-discharge voltage when compared to untreated battery grade copper foil based on standard lithium ion battery half-cell testing at 25° C. and a discharge rate of 2C or greater. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The polymer film attached to the metal layer can be used to form a current collector for an energy storage device. In one embodiment, useful polymer compositions for the polymer film can include polyimide (PI), polyamide-imide (PAI), poly(ester-imide), poly(amide-ester-imide), polycarbonate (PC), polyethylene naphthalate (PEN), polystyrene (PS), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polyethylene terephthalate glycol (PETG), polycyclohexylene dimethylene terephthalate glycol (PCTG), polyetherimide (PEI), polysulfone, polyethersulfone, polyarylsulfone, polyetherketoneketone (PEKK), such as polyaryletherketone (PAEK) and polyetheretherketone (PEEK), and cyclic olefin copolymers. In one embodiment, polymer compositions having imide groups are particularly useful. Polymer compositions having imide groups and including aromatic monomers are typically very thermally, chemically, and electrochemically stable at the low potentials (anodes) and high potentials (cathodes) used in lithium ion batteries.

[0009] Depending on the context, as used herein, "diamine" is intended to mean (i) the unreacted form (i.e., the diamine monomer); (ii) the partially reacted form (i.e., one or more portions of an oligomer or other polymer precursor derived or otherwise derived from the diamine monomer), or (iii) the fully reacted form (one or more portions of a polymer derived or otherwise derived from the diamine monomer). The diamine can be functionalized at one or more sites, depending on the particular embodiment selected in the practice of the invention.

[0010] Indeed, the term "diamine" is not intended to be limiting (or to be taken literally) with respect to the number of amine moieties in the diamine component. For example, (ii) and (iii) above include polymeric materials that may have two, one, or zero amine moieties. Alternatively, the diamine may be functionalized with additional amine moieties (in addition to the amine moieties at the ends of the monomers that react with the dianhydride to grow the polymer chain). Such additional amine moieties could be used to crosslink the polymer or to provide other functional groups to the polymer.

[0011] Similarly, as used herein, the term "dianhydride" is intended to mean a (complementary) component that reacts with a diamine, which can react in combination to form an intermediate that can then be hardened into a polymer. Depending on the context, as used herein, "anhydride" can refer not only to the anhydride moiety itself, but also to a precursor of an anhydride moiety, such as (i) a pair of carboxylic acid groups, which can be converted to an anhydride by dehydration or similar type of reaction; or (ii) an acid halide (e.g., chloride) ester functional group (or any other functional group now known or developed in the future) that can be converted to an anhydride functional group.

[0012] Depending on the context, "dianhydride" can mean (i) the unreacted form (i.e., the dianhydride monomer, whether the anhydride functionality is in true anhydride form or in a precursor anhydride form as discussed in the preceding paragraph above); (ii) the partially reacted form (i.e., one or more portions of an oligomer or other partially reacted or precursor polymer composition reacted from or otherwise derived from the dianhydride monomer), or (iii) the fully reacted form (one or more portions of a polymer derived from or otherwise derived from the dianhydride monomer).

[0013] The dianhydride may be functionalized with one or more sites, depending on the particular embodiment selected in the practice of the invention. Indeed, the term "dianhydride" is not intended to be limiting (or to be taken literally) with respect to the number of anhydride sites in the dianhydride component. For example, (i), (ii) and (iii) (in the paragraph above) include organic materials that may have two, one or zero anhydride sites, depending on whether the anhydride is in a precursor state or in a reacted state. Instead, the dianhydride component may be functionalized with additional anhydride-type sites (in addition to the anhydride site that reacts with the diamine to give the polymer). Such additional anhydride sites could be used to crosslink the polymer or to give other functional groups to the polymer.

[0014] The polymer film can be made using any one of several polymer manufacturing processes. It would be impossible to discuss or describe all possible manufacturing processes useful in the practice of the present invention. It should be understood that the monomer system of the present invention can impart the above-mentioned advantageous properties in a variety of manufacturing processes. The composition of the present invention can be manufactured as described herein, or can be easily manufactured in any one of many (possibly countless) ways by one skilled in the art, using any conventional or non-conventional manufacturing technique.

[0015] Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, suitable methods and materials are described herein.

[0016] When an amount, concentration or other value or parameter is given as a range, a preferred range or a list of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed from any pair of any upper range or preferred value and any lower range or preferred value, whether or not the ranges are separately disclosed. When a range of numerical values ​​is recited herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within the range. The scope of the present invention is not intended to be limited to the specific values ​​recited when defining the range.

[0017] It should be understood that when describing particular polymers, applicants may refer to the polymers by the monomers used to make them or the amounts of monomers used to make them. Such descriptions may not include the particular nomenclature used to describe the final polymer, or may not include product-by-process terminology, but any such reference to monomers and amounts should be interpreted to mean that the polymer is made from those monomers or amounts of monomers, and the corresponding polymers and their compositions.

[0018] The materials, methods, and examples herein are illustrative only and, except as specifically stated, are not intended to be limiting.

[0019] As used herein, the terms "comprise", "includes", "includes", "including", "having", "having" or any other variations thereof are intended to cover non-exclusive inclusions. For example, a method, process, article, or apparatus that includes a list of elements is not necessarily limited to only those elements and may include other elements not expressly listed or inherent to such method, process, article, or apparatus. Furthermore, unless expressly stated to the contrary, "or" means an inclusive "or" and not an exclusive "or". For example, a condition A or B is satisfied by any one of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist).

[0020] The use of "a" or "an" is also used to describe elements and components of the present invention. This is done merely for convenience and to give a general sense of the invention. The description should be read to include one or at least one, and the singular also encompasses the plural unless it is clear that this is meant otherwise.

[0021] Terms such as first, second, third, etc. may be used herein to describe various elements, components, regions, layers, and / or sections, but it will be understood that these elements, components, regions, layers, and / or sections should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer, and / or section from another element, component, region, layer, and / or section. Thus, a first element, component, region, layer, and / or section could be referred to as a second element, component, region, layer, and / or section without departing from the teachings of the present invention. Similarly, the terms "top" and "bottom" are only relative to each other. If elements, components, layers, etc. are reversed, it will be fully understood that what was "bottom" before being reversed will be "top" after being reversed, and vice versa. When an element is said to be "on" or "disposed on" another element, it means that it is located above or below the object part, but does not inherently mean that it is located on the upper side of the object part based on the direction of gravity; it may be directly on the other element, or there may be intervening elements in between. In contrast, when an element is said to be "directly on" or "directly disposed on" another element, there are no intervening elements present.

[0022] Furthermore, when an element, component, region, layer and / or region is said to be "between" two elements, components, regions, layers and / or regions, it will be understood that it may be the only element, component, region, layer and / or region between the two elements, components, regions, layers and / or regions or that one or more intervening elements, components, regions, layers and / or regions may also be present.

[0023] Organic solvents Useful organic solvents for the synthesis of the polymers of the present invention are preferably capable of dissolving the polymer precursor materials. Such solvents should also have a relatively low boiling point, such as less than 225°C, so that the polymers can be dried at moderate (i.e., more convenient and less costly) temperatures. Boiling points less than 210, 205, 200, 195, 190, or 180°C are preferred.

[0024] Useful organic solvents include N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), methyl ethyl ketone (MEK), N,N'-dimethylformamide (DMF), dimethylsulfoxide (DMSO), tetramethylurea (TMU), glycol ethyl ether, diethylene glycol diethyl ether, 1,2-dimethoxyethane (monoglyme), diethylene glycol dimethyl ether (diglyme), 1,2-bis-(2-methoxyethoxy)ethane (triglyme), gamma-butyrolactone, and bis-(2-methoxyethyl)ether, tetrahydrofuran (THF), ethyl acetate, hydroxyethyl acetate glycol monoacetate, acetone, and mixtures thereof. In one embodiment, preferred solvents include N-methylpyrrolidone (NMP) and dimethylacetamide (DMAc).

[0025] Diamine In one embodiment, aromatic diamines can be used to form polymers having imide groups. Examples of aromatic diamines include 2,2'-bis(trifluoromethyl)benzidine (TFMB), 2,2'-bis-(4-aminophenyl)hexafluoropropane, 4,4'-diamino-2,2'-trifluoromethyldiphenyloxide, 3,3'-diamino-5,5'-trifluoromethyldiphenyloxide, 9,9'-bis(4-aminophenyl)fluorene, 4,4'-trifluoromethyl-2,2'-diaminobiphenyl, 4,4'-oxy-bis[2-trifluoromethyl]benzenamine](1,2 ,4-OBABTF), 4,4'-oxy-bis[3-trifluoromethyl)benzenamine], 4,4'-thiobis[(2-trifluoromethyl)benzenamine], 4,4'-thiobis[(3-trifluoromethyl)benzenamine], 4,4'-sulfoxyl-bis[(2-trifluoromethyl)benzenamine], 4,4'-sulfoxyl-bis[(3-trifluoromethyl)benzenamine, 4,4'-keto-bis[(2-trifluoromethyl)benzenamine], 1,1-bis[4'-(4"-amino- 2"-trifluoromethylphenoxy)phenyl]cyclopentane, 1,1-bis[4'-(4"-amino-2"-trifluoromethylphenoxy)phenyl]cyclohexane, 2-trifluoromethyl-4,4'-diaminodiphenyl ether; 1,4-(2'-trifluoromethyl-4',4"-diaminodiphenoxy)benzene, 1,4-bis(4'-aminophenoxy)-2-[(3',5'-ditrifluoromethyl)phenyl]benzene (6F-amine), 1,4-bis[2'-cyano-3'("4-amino Examples of suitable fluoro-4,4'-diamino-diphenylmethane include 2,2-bis[4(4-aminophenoxy)phenyl]phthalein-3',5'-bis(trifluoromethyl)anilide (6FADAP), and 3,3',5,5'-tetrafluoro-4,4'-diamino-diphenylmethane (TFDAM).

[0026] Other useful diamines include 4,4'-diaminobiphenyl, 4,4"-diaminoterphenyl, 4,4'-diaminobenzanilide (DABA), 4,4'-diaminophenyl benzoate, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-diaminodiphenyl ether (ODA), 3,4'-diamino Examples of suitable diamines include diphenyl ether, 4,4'-isopropylidenediamine, 2,2'-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4-aminophenyl-3-aminobenzoate, bis(p-β-amino-t-butylphenyl)ether, and p-bis-2-(2-methyl-4-aminopentyl)benzene. In one embodiment, the diamine is a triamine such as N,N-bis(4-aminophenyl)-n-butylamine, N,N-bis(4-aminophenyl)methylamine, or N,N-bis(4-aminophenyl)aniline.

[0027] Other useful diamines include 1,2-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene (RODA), 1,2-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-3-(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1-(4-aminophenoxy)-4-(3-aminophenoxy)benzene, 2,2-bis(4-[4-aminophenoxy]phenyl)propane (BAPP), 2,2'-bis(4-phenoxyaniline)isopropylidene.

[0028] Other useful diamines include p-phenylenediamine (PPD), m-phenylenediamine (MPD), 2,5-dimethyl-1,4-diaminobenzene, 2,5-dimethyl-1,4-phenylenediamine (DPX), 1,4-naphthalenediamine, 1,5-naphthalenediamine, 1,5-diaminonaphthalene, m-xylylenediamine, and p-xylylenediamine.

[0029] Other useful diamines for forming polymers having imide groups can include aliphatic diamines such as 1,2-diaminoethane, 1,6-diaminohexane (HMD), 1,4-diaminobutane, 1,5-diaminopentane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane (DMD), 1,11-diaminoundecane, 1,12-diaminododecane (DDD), 1,16-hexadecamethylenediamine, 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, trans-1,4-diaminocyclohexane (CHDA), isophoronediamine (IPDA), bicyclo[2.2.2]octane-1,4-diamine, and combinations thereof. Other aliphatic diamines suitable for the practice of the present invention include those having 6 to 12 carbon atoms or combinations of long and short chain diamines, so long as both the malleability and flexibility of the polymer are maintained. Long chain aliphatic diamines may provide increased flexibility.

[0030] Other useful diamines for forming polymers having imide groups include cycloaliphatic diamines (which may be fully or partially saturated), such as cyclobutane diamines (e.g., cis- and trans-1,3-diaminocyclobutane, 6-amino-3-azaspiro[3.3]heptane, and 3,6-diaminospiro[3.3]heptane), bicyclo[2.2.1]heptane-1,4-diamine, isophorone diamine, and bicyclo[2.2.2]octane-1,4 diamine. Other cycloaliphatic diamines include cis-1,4-cyclohexanediamine, trans-1,4-cyclohexanediamine, 1,4-bis(aminomethyl)cyclohexane, 4,4'-methylenebis(cyclohexylamine), 4,4'-methylenebis(2-methyl-cyclohexylamine), and bis(aminomethyl)norbornane.

[0031] dianhydride In one embodiment, aromatic dianhydrides can be used to form polymers with imide groups. The dianhydrides can be used in their tetraacid form (or as mono-, di-, tri- or tetraesters of the tetraacid) or as their diester acid halides (chlorides). However, in some embodiments, the dianhydride forms can be preferred, as they are generally more reactive than the acids or esters.

[0032] Examples of suitable aromatic dianhydrides include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzimidazole dianhydride, 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzoxazole dianhydride, 2-(3',4'-dicarboxyphenyl)-5,6-dicarboxybenzothiazole dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,3,3', 4'-Benzophenonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 4,4'-thio-diphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)sulfoxide dianhydride (DSDA), bis(3,4-dicarboxyphenyloxadiazole-1,3 ,4)-p-phenylene dianhydride, bis(3,4-dicarboxyphenyl)-2,5-oxadiazole-1,3,4-dianhydride, bis(3',4'-dicarboxydiphenylether)-2,5-oxadiazole-1,3,4-dianhydride, 4,4'-oxydiphthalic anhydride (ODPA), bis(3,4-dicarboxyphenyl)thioether dianhydride, bisphenol A dianhydride (BPADA), bisphenol S dianhydride, bis-1,3-isobenzofurandione, 1,4-bis( 4,4'-oxyphthalic anhydride)benzene, bis(3,4-dicarboxyphenyl)methane dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, 1,3-bis(4,4'-oxydiphthalic anhydride)benzene, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), and 9,9-bis(trifluoromethyl)-2,3,6,7-xanthenetetracarboxylic dianhydride.

[0033] Other useful dianhydrides include 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, bicyclo-[2,2,2]-octene-(7)-2,3,5,6-tetracarboxylic-2,3,5,6-dianhydride, cyclopentadienyltetracarboxylic dianhydride, ethylenetetracarboxylic dianhydride, pyromellitic dianhydride (PMDA), tetrahydrofurantetracarboxylic dianhydride, 2,6- Examples of the dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride include dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, phenanthrene-1,8,9,10-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride, and thiophene-2,3,4,5-tetracarboxylic dianhydride.

[0034] In one embodiment, the dianhydride for forming the polymer having imide groups can be a cycloaliphatic dianhydride such as cyclobutane-1,2,3,4-tetracarboxylic dianhydride (CBDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), hexahydro-4,8-ethano-1H,3H-benzo[1,2-c:4,5-c']difuran-1,3,5,7-tetrone (BODA), 3-(carboxymethyl)-1,2,4-cyclopentanetricarboxylic 1,4:2,3-dianhydride (TCA), and meso-butane-1,2,3,4-tetracarboxylic dianhydride.

[0035] In one embodiment, when the polymer further comprises an additional aromatic amide component, suitable additional dicarbonyl chlorides for forming the polymer can include terephthaloyl chloride (TPCI), isophthaloyl chloride (IPCI), biphenyldicarbonyl chloride (BPCI), naphthalene dicarbonyl chloride, terphenyldicarbonyl chloride, 2-fluoro-terephthaloyl chloride, and trimellitic anhydride.

[0036] In one embodiment, poly(amide-ester-imide)s can be prepared from polyols that can be reacted with carboxylic acids or ester acid halides to form ester linkages.

[0037] The dihydric alcohol component can be almost any alcoholic diol that contains two esterifiable hydroxyl groups. It can also include mixtures of suitable diols. Diols suitable for use herein include, for example, ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, and the like.

[0038] The polyhydric alcohol component may be almost any polyhydric alcohol that contains at least three hydroxyl groups that can be esterified to provide the advantages of the above-mentioned synthesis process of the present invention. Mixtures of such polyhydric alcohols may be suitably used. Suitable polyhydric alcohols include, for example, tris(2-hydroxyethyl)isocyanurate, glycerin, 1,1,1-trimethylolethane, 1,1,1-trimethylolpropane, and mixtures thereof.

[0039] In some cases, useful diamine and dianhydride monomers contain ester groups. Examples of these monomers include diamines such as 4-aminophenyl-4-aminobenzoate and 4-amino-3-methylphenyl-4-aminobenzoate, and dianhydrides such as p-phenylene bis(trimellitate) dianhydride.

[0040] In some cases, useful diamine and dianhydride monomers include amide groups.Examples of these monomers include diamines such as 4,4'-diaminobenzamide (DABAN) and dianhydrides such as N,N'-(2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxamide) and N,N'-(9H-fluoren-9-ylidene-4,1-phenylene)bis[1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxamide].

[0041] Higher order copolymers having imide groups can include any of the above monomers.

[0042] Imidization Catalyst In one embodiment, an imidization catalyst (sometimes referred to as an "imidization promoter") can be used as a conversion chemical that can help reduce the imidization temperature and time to form a polymer with imide groups. The polyamic acid casting solution of the present invention includes both a polyamic acid solution combined with an amount of a conversion chemical. Conversion chemicals that have been found to be useful in the present invention include, but are not limited to, (i) one or more dehydrating agents and / or co-catalysts, such as aliphatic acid anhydrides (such as acetic anhydride, trifluoroacetic anhydride, propionic anhydride, monochloroacetic anhydride, bromoadipic anhydride, etc.), and aromatic acid anhydrides; and (ii) one or more imidization catalysts, such as aliphatic tertiary amines (such as triethylamine), aromatic tertiary amines (such as dimethylaniline, N,N-dimethylbenzylamine, etc.), and heterocyclic tertiary amines (such as pyridine, α,β,γ-picoline, 3,5-lutidine, 3,4-lutidine, isoquinoline, etc.), and guanidines (such as tetramethylguanidine). In one embodiment, the imidization catalyst does not include a diazole. Other useful dehydrating agents include diacetyl oxide, butyryl oxide, benzoyl oxide, 1,3-dicyclohexylcarbodiimide, N,N-dicyclohexylcarbodiimide, benzenesulfonyl chloride, thionyl chloride, and phosphorus pentoxide. In some embodiments, the dehydrating agent can also function as a catalyst to enhance the reaction rate for imidization. The anhydride that dehydrates the material is typically used in slight molar excess over the amount of amic acid groups present in the polyamic acid solution. In one embodiment, the amount of dehydrating agent used is typically about 2.0 to 4.0 moles per equivalent of polyamic acid formula units. Generally, the same amount of tertiary amine catalyst is used. The ratio of these catalysts in the polyamic acid solution and their concentrations will affect the imidization reaction rate and film properties. The polymer film can have the imidization catalyst present in the polymer film in an amount ranging from 1 parts per billion (ppb) to 1 weight percent, from 10 ppb to 0.1 weight percent, or from 100 ppb to 0.01 weight percent.

[0043] Conductive Filler In one embodiment, the conductive filler can include metals (such as gold, silver, copper, etc.), conductive mixed metal oxides (such as copper oxide, superconductor oxides, indium tin oxide, antimony tin oxide, mixed titanium / tin / zirconium oxide, etc.), organic compounds such as polyaniline, polythiophene, polypyrrole, polyphenylene vinylene, polydialkylfluorene, carbon black, graphite, graphene, multi-walled and single-walled carbon nanotubes and other nanotube structures, and carbon nanofibers. In one embodiment, the conductive filler can be an inorganic filler, an organic filler, or a mixture thereof.

[0044] In one embodiment, the conductive filler is carbon black. In one embodiment, the conductive filler is selected from the group consisting of acetylene black, ultra-abrasive furnace black, conductive furnace black, conductive channel type black, carbon nanotubes, carbon fibers, fine thermal black, and mixtures thereof. For carbon black, oxygen complexes on the surface of the carbon particles act as an electrical insulating layer. Therefore, low volatile content is generally desirable for high conductivity. However, the difficulty of dispersing carbon black must also be considered. Surface oxidation promotes the deagglomeration and dispersion of carbon black. In some embodiments, when the conductive filler is carbon black, the carbon black has a volatile content of 1% or less.

[0045] Other fillers In one embodiment, other fillers for the polymer film can include other inorganic and organic fillers not mentioned above for the conductive filler. Inorganic fillers can include thermally conductive fillers, such as metal oxides, inorganic nitrides, and metal carbides. In one embodiment, inorganic fillers can include metal oxides, such as diamond, clay, talc, sepiolite, mica, dicalcium phosphate; magnetic metal oxides, transparent conductive oxides, and fumed metal oxides. In one embodiment, inorganic fillers can include inorganic oxides, such as oxides of silicon, aluminum, and titanium, hollow (porous) silicon oxide, antimony oxide, zirconium oxide, indium tin oxide, antimony tin oxide, mixed titanium / tin / zirconium oxide, and binary, ternary, quaternary, and higher oxides of one or more cations selected from silicon, titanium, aluminum, antimony, zirconium, indium, tin, zinc, niobium, and tantalum. In one embodiment, particle composites (eg, single or multiple core / shell structures) can be used in which one oxide encapsulates another oxide within a particle.

[0046] In one embodiment, the inorganic fillers can include boron nitride, aluminum nitride, ternary or higher compounds containing boron, aluminum, and nitrogen, gallium nitride, silicon nitride, aluminum nitride, zinc selenide, zinc sulfide, zinc telluride, silicon carbide, and combinations thereof, or other ceramic compounds such as higher compounds containing multiple cations and multiple anions, and can include oxycarbides and oxynitrides.

[0047] In one embodiment, the filler for the polymer has a median particle size, d, in the range of 0.1 to 10 μm, 0.1 to 5 μm, 0.2 to 5 μm, or 0.2 to 3 μm. 50 The filler size can be measured using a laser particle size analyzer while the filler is dispersed in an organic solvent (optionally with the aid of a dispersant, adhesion promoter, and / or coupling agent). The median particle size, d 50is the equivalent spherical diameter based on the median volume distribution of the particles. If the median particle size is smaller than 0.1 μm, the filler particles may tend to aggregate or become unstable in the organic solvent used to make the polymer. If the median particle size of the aggregated particles is greater than 10 μm, the dispersion of the filler component in the polymer film may be too inhomogeneous (or inappropriately large for the thickness of the film). A relatively inhomogeneous dispersion of the filler component in the film may result in poor mechanical elongation of the film, poor flex life of the film, and / or low dielectric strength. In one embodiment, the filler may require extensive milling and filtration to break up undesirable particle agglomerations, as is typical when attempting to disperse some fillers into a polymer matrix. Such milling and filtration may be expensive and may not remove all undesirable agglomerates. In one embodiment, the average aspect ratio of the filler may be 1 or greater. In some embodiments, the filler is selected from the group consisting of acicular fillers (acicular), fibrous fillers, platelet fillers, polymeric fibers, and mixtures thereof. In one embodiment, the filler can have an aspect ratio of at least 1, at least 2, at least 4, at least 6, at least 8, at least 10, at least 12, at least 15, at least 25, at least 50, at least 100, at least 200, or at least 300 to 1.

[0048] In one embodiment, the filler includes a mixture or blend of fillers having any number of particle types, particle sizes and particle shapes, where the mixture or blend can be of the same type of filler or different types of fillers.

[0049] In one embodiment, the filler can be coated with a coupling agent. For example, the filler particles can be coated with an acrylic or methacrylic coupling agent derived from aminosilane, phenylsilane, or the corresponding alkoxysilane. The trimethylsilyl surface capping agent can be introduced to the particle surface by reaction of the filler with hexamethyldisilazane. In one embodiment, the filler can be coated with a dispersing agent. In one embodiment, the filler can be coated with a combination of a coupling agent and a dispersing agent. Alternatively, the coupling agent, dispersing agent, or a combination thereof can be directly incorporated into the polymer film and not necessarily coated on the filler.

[0050] Polymer Film In one embodiment, the polymer film, which is a polyimide film, can be produced by combining a diamine and a dianhydride (either monomer or other polyimide precursor form) with a solvent to form a polyamic acid (also called polyamic acid) solution. The dianhydride and diamine can be combined in a molar ratio of about 0.90 to 1.10. The molecular weight of the polyamic acid formed therefrom can be adjusted by adjusting the molar ratio of the dianhydride to the diamine.

[0051] In one embodiment, the polyamic acid casting solution is derived from a polyamic acid solution. The polyamic acid casting solution and / or the polyamic acid solution are combined with a conversion chemical such as (i) one or more dehydrating agents, such as fatty acid anhydrides (such as acetic anhydride) and / or aromatic acid anhydrides; and (ii) one or more catalysts, such as aliphatic tertiary amines (such as triethylamine), aromatic tertiary amines (such as dimethylaniline), and heterocyclic tertiary amines (such as pyridine, picoline, isoquinoline). The anhydride dehydrating agent is often used in molar excess relative to the amount of amic acid groups in the polyamic acid. The amount of acetic anhydride used is typically about 2.0 to 4.0 moles per equivalent (repeating unit) of polyamic acid. Generally, the same amount of tertiary amine catalyst is used. A filler dispersed or suspended in a solvent as described above is then added to the polyamic acid solution.

[0052] In one embodiment, the polyamic acid solution is dissolved in an organic solvent at a concentration of about 5.0 or 10 percent to 15, 20, 25, 30, 35, or 40 percent by weight. In one embodiment, a slurry is prepared containing conductive filler, where the slurry has a conductive filler content ranging from 0.1-70, 0.5-60, 1-55, 2-50, or 5-45 percent by weight. The slurry may or may not be milled using a ball mill to reach the desired particle size. The slurry may or may not be filtered to remove any remaining large particles. The polyamic acid solution may be produced by methods well known in the art. The polyamic acid solution may or may not be filtered. In some embodiments, the solution is mixed with the filler slurry in a high shear mixer. If the polyamic acid solution is produced with a slight excess of diamine, additional dianhydride solution may or may not be added to increase the viscosity of the mixture to a desired level for film casting. The amounts of polyamic acid solution and filler slurry can be adjusted to achieve the desired loading level in the cured film. In some embodiments, the mixture is cooled below 10° C. and mixed with the conversion chemicals before casting.

[0053] The solvated mixture (polyamic acid casting solution) can then be cast or coated onto a support, such as an endless belt or a rotating drum, to obtain a partially imidized film. Alternatively, it can be cast onto a polymeric support, such as PET, other forms of Kapton® polyimide film (e.g., Kapton® HN or Kapton® E film), or other polymeric support. The gel film can be peeled off the drum or belt placed on a tenter frame and cured in an oven using convection and radiant heat to remove the solvent and complete the imidization to a solids level of more than 98%. The film can then be separated from the support, stretched, such as by tentering, and continued heating (drying and curing) to obtain a polyimide film.

[0054] Useful methods for producing polyimide films can be found in U.S. Pat. No. 5,399,433 and U.S. Pat. No. 5,499,463, which are incorporated herein by reference for all their teachings. Many variations are also possible, such as: (a) The diamine and dianhydride components are premixed together and then added portionwise to the solvent while the mixture is being stirred. (b) A method (as opposed to (a) above) in which the solvent is added to a stirred mixture of the diamine and dianhydride components. (c) A method in which the diamine is dissolved exclusively in a solvent and then the dianhydride is added thereto in a ratio which makes it possible to control the reaction rate. (d) A method in which the dianhydride component is dissolved exclusively in a solvent and then the amine component is added thereto in a ratio which makes it possible to control the reaction rate. (e) A method in which the diamine and dianhydride components are dissolved separately in a solvent and then the solutions are mixed in a reactor. (f) A process in which a polyamic acid containing an excess of an amine component and another polyamic acid containing an excess of a dianhydride component are preformed and then reacted with each other in a reactor in a manner that allows, inter alia, the formation of non-random or block copolymers. (g) A specific portion of the amine and dianhydride components are reacted first and then the remaining diamine component is reacted, or vice versa. (h) A method in which a conversion chemical (catalyst) is mixed with a polyamic acid to form a polyamic acid casting solution, which is then cast to form a gel film. (i) A process in which the ingredients are added partially or wholly in any order, either in some or all of the solvent, and some or all of any ingredient may be added as a solution in some or all of the solvent. (j) One of the dianhydride components is first reacted with one of the diamine components to give a first polyamic acid, then another dianhydride component is reacted with another amine component to give a second polyamic acid, and the amic acids are then combined in any one of several ways prior to film formation.

[0055] In one embodiment, the solvated mixture (polyamic acid casting solution) can be mixed with a crosslinked precursor and then cast to form a polymer film. In one embodiment, the polymer film contains in the range of 80-99% by weight crosslinked polymer. In some embodiments, the polymer film contains between any two of 80, 85, 90, 95, and 99% by weight crosslinked polymer, inclusive. In yet another embodiment, the polymer film contains 91-98% by weight crosslinked polymer.

[0056] In one embodiment, the crosslinking reaction includes compounds, such as highly reactive amines, that can participate in crosslinking reactions that crosslink polymer chains in the film. In one embodiment, heat may be used to crosslink the polymer. In one embodiment, irradiation with a light source may be used to crosslink the polymer by a photoinitiated process. In one embodiment, additional highly reactive chemical species may be used to crosslink the polymer. In one embodiment, any combination of these processes may be used to crosslink the polymer.

[0057] Crosslinking of a polymer can be determined by a variety of methods. In one embodiment, the gel fraction of a polymer can be determined by using an equilibrium swelling method, comparing the weight of a dried film before and after crosslinking. In one embodiment, the crosslinked polymer can have a gel fraction ranging from 20-100%, 40-100%, 50-100%, 70-100%, or 85-100%. In one embodiment, the crosslinked network can be identified using rheological methods. Oscillatory time sweep measurements at specific strains, frequencies, and temperatures can be used to confirm the formation of a crosslinked network. Initially, the loss modulus (G'') value is higher than the storage modulus (G') value, indicating that the polymer solution behaves like a viscous liquid. Over time, the formation of a crosslinked polymer network is evidenced by the intersection of the G' and G'' curves. The intersection, called the "gel point," represents when the elastic component predominates over the viscous component.

[0058] In one embodiment, the conductive filler is first dispersed in a solvent to form a slurry. The slurry is then dispersed in a polyamic acid solution. In one embodiment, the concentration of the conductive filler relative to the polyimide (in the final film) ranges from 5 to 65 wt%, 5 to 50 wt%, 10 to 40 wt%, or 15 to 35 wt%, based on the total weight of the polymer film. In one embodiment, the concentration of the conductive filler relative to the polyimide (in the final film) is at least 5 wt%, at least 10 wt%, at least 15 wt%, at least 20 wt%, or at least 25 wt%, based on the total weight of the polymer film. The composition of the cured film can be calculated from the composition of the components in the mixture, excluding the DMAc solvent (which is removed during curing), and taking into account the removal of water during the conversion of the polyamic acid to polyimide. When a conductive filler is used, the conductivity of the polyimide film increases as the concentration of the filler increases. In one embodiment, the conductive polymer film can have a surface resistivity of 1 megaohm / sq or less, 0.5 megaohm / sq or less, 0.1 megaohm / sq or less, or 50,000 megaohm / sq or less. One skilled in the art will appreciate that in addition to loading level, the characteristics of the conductive fillers, such as particle size, morphology, aspect ratio, surface oxidation, etc., affect the surface resistivity of polymer films containing them.

[0059] In one embodiment, blending of the filler slurry with the polyamic acid solution to form the filled polyamic acid casting solution is performed using high shear mixing. In this embodiment, if the filler is present in the final film at more than 65 weight percent, the film may be too brittle and may not be flexible enough to form a free-standing, mechanically strong, flexible sheet. Furthermore, if the filler is present at levels less than 5 weight percent, the film formed therefrom may not be sufficiently conductive.

[0060] In one embodiment, the casting solution can further include any one of a number of additives, such as processing aids (e.g., oligomers), antioxidants, light stabilizers, flame retardant additives, antistatic agents, heat stabilizers, UV absorbers, or various toughening agents.

[0061] In one embodiment, the coextrusion process can be used to form multilayer polymer films having two or more layers, such as a three-layer polymer film having an inner core layer sandwiched between two outer layers. In this process, for a three-layer polyimide film, the finished polyamic acid solution is filtered and pumped to a slot die where the streams are split to form the first and second outer layers of the three-layer coextruded film. In some embodiments, the second stream of polymer is filtered and then pumped to a casting die to form the central polymer core layer of the three-layer coextruded film. The flow rate of the solution can be adjusted to achieve a desired layer thickness. In one embodiment, the polymer composition and filler content of the first and second outer layers are the same, while in another embodiment, the polymer composition and / or filler content of the first and second outer layers are different. In some embodiments, the polymer composition and filler content of the core layer can be the same or different from one or both of the outer layers.

[0062] In one embodiment, the multilayer film is made by co-extruding the first outer layer, the core layer, and the second outer layer. In some embodiments, the layers are extruded through a single or multiple cavity extrusion die. In another embodiment, the multilayer film is made using a single cavity die. If a single cavity die is used, the laminar flow of the stream should be of high enough viscosity to prevent mixing of the streams and provide uniform stratification. In some embodiments, the multilayer film is made by casting from a slot die onto a moving stainless steel belt. In one embodiment, for polymers with imide groups, the belt is then passed through a convection oven to evaporate the solvent and partially imidize the polymer to produce a "green" film. The green film can be stripped from the casting belt and wound up. The green film can then be passed through a tenter oven to provide a fully cured polymer film. In some embodiments, shrinkage can be minimized during tentering by restraining the film along the edges (i.e., using clips or pins).

[0063] In one embodiment, the outer layer of the present invention may also be applied to a core layer during an intermediate manufacturing stage in producing a polymeric film, such as a gel film or green film.

[0064] The term "gel film" when forming imide-containing polymers refers to polyamic acid sheets that contain volatiles, primarily solvents, to such an extent that the polyamic acid is in a gel-swollen or rubbery state, and may be formed in a chemical conversion process. The volatile content is typically in the range of 70-90% by weight of the gel film, and the polymer content is typically in the range of 10-30% by weight. The final film becomes "free-standing" at the gel film stage. It can be stripped from the support on which it was cast and heated to a final cure temperature. Gel films generally have an amic acid to imide ratio of 10:90 to 50:50, most often 30:70.

[0065] The gel film structure can be made by the method described in U.S. Patent No. 5,399,636. This patent discloses mixing chemical converting agents and catalysts, such as lower fatty acid anhydrides and tertiary amines, into a polyamic acid solution at low temperature. This is followed by casting the polyamic acid solution in the form of a film onto a casting drum. The film is gently heated after casting, for example at 100° C., to activate the converting agents and catalysts to transform the cast film into a polyamic acid / polyimide gel film.

[0066] Another type of polymer film is the "green film" which, for polyimide films, is partially polyamic acid and partially polyimide and can be formed in a thermal conversion process. The green film generally contains about 50-75% by weight polymer and 25-50% by weight solvent. In general, it should be strong enough to be substantially self-supporting. The green film can be made by casting a polyamic acid solution into a film form on a suitable support such as a casting drum or belt and removing the solvent by gentle heating at up to 150°C. A small percentage of the amic acid units in the polymer, for example up to 25%, can be converted to imide units.

[0067] The application of the polymeric film of the present invention can be accomplished in many ways. Such methods include the use of a slot die, dip coating or kiss-roll coating of the film followed by metering with a doctor knife, doctor roll, squeeze roll, or air knife. The coating can also be applied by brushing or spraying. By using such techniques, it is possible to make both one-sided and two-sided coated laminates. In making a two-sided coated structure, the coating can be applied to two sides of the polymer either simultaneously or successively before proceeding to the polymer curing and drying steps.

[0068] The thickness of the polymer film can be adjusted depending on the intended purpose or end use specifications of the film. In one embodiment, the polymer film has a layer thickness in the range of 1 to 300 μm, 2 to 200 μm, 5 to 150 μm, 10 to 100 μm, or 20 to 80 μm.

[0069] In one embodiment, for a two-layer or three-layer polymer film, the core layer has a thickness in the range of 0.75 to 225 μm, 1.5 to 150 μm, 3.75 to 112.5 μm, or 7.5 to 75 μm, and the outer layers have a thickness in the range of 0.25 to 75 μm, 0.5 to 50 μm, 1.25 to 37.5 μm, or 2.5 to 25 μm, respectively. In one embodiment, for a three-layer film, the thicknesses of the outer layers may be the same or different.

[0070] Current collector In one embodiment, a current collector for an energy storage device can include a polymer film and a metal layer adhered to the polymer film. The current collector provides a path for supplying charge (electricity) to an external circuit. However, in LIBs, the current collectors are passive elements. This is because they are not connected to the Li + This means that it does not participate in the intercalation reaction of ions. Therefore, thin and light materials are preferred for the current collector so that the gravimetric and volumetric energy densities of the cell can remain high. The material must be ionically insulating and electronically conductive, and must maintain good chemical and electrochemical stability in the electrolyte during operation of the battery. Other requirements include providing a mechanically robust framework for the cell structure and must adhere well to the electrode slurry. In one embodiment, the current collector can include a polymer film with metal layers adhered to both sides of the polymer film.

[0071] The current collector can be formed as a double-sided metal-clad polymer film by any number of well-known processes. In one embodiment, a metal plating process can be used to form a metal-clad laminate with a polymer film, such as a polyimide film. In one embodiment, the polyimide film includes a thermoplastic polyimide layer. A metal layer can be formed on the thermoplastic polyimide layer of the polymer film by plating a thin metal layer. In one embodiment, the thin metal layer can be 10 μm or less, 5 μm or less, 3 μm or less, or 1 μm or less. By forming a metal layer on the polymer film using a plating process, a smoother interface can be formed between the current collector and the electrode. Conventional lamination of metal foil to polymer film relies on the surface roughness of the foil to obtain good adhesion to the polymer film, but sometimes a roughness greater than the thickness of the thin metal layer is required.

[0072] In one embodiment, the polymer film can be bonded to the first and second metal layers in a plating process to form a double-sided metal-clad polymer film. The plating process can include electroless plating followed by electrolytic plating. The electroless plating process is used to form an initial metal layer, typically less than 250 nm, or thick enough to impart uniform conductivity across the surface. An electrolytic plating process is then used to build the metal layer to the desired thickness and obtain a favorable Cu grain structure for good conductivity. In one embodiment, the surface of the polymer film to be plated can be plasma treated before the metal layer is formed. Thus, the metal-clad polymer film formed includes a polymer film and two thin conductive layers. In one embodiment, for a multi-layer polymer film, the use of a thermoplastic polymer layer as an outer layer to bond to the metal layer allows for strong adhesion between the polymer film and the metal layer while still providing a smooth interface between the layers and without the use of additional primer or adhesive layers in between.

[0073] In another embodiment, other metal plating processes can be used to form a seed layer prior to electroplating. In one embodiment, atomic layer deposition (ALD) can be used to form a conductive seed layer of a metal such as Pd or Ag prior to electroplating. In one embodiment, physical vapor deposition or sputtering can be used to bond the polymer film to the metal layer. Physical vapor deposition occurs when a seed layer is deposited from a solid onto a polymer film by evaporating a solid source under vacuum conditions. In one embodiment, chemical vapor deposition can be used to bond the polymer film to the metal layer. In this process, deposition species are introduced into the deposition chamber in a gas phase.

[0074] In one embodiment, the polymer film can be bonded to the first metal layer by electrochemically depositing a metal layer directly onto the polymer film (direct metallization). The term "electrochemically depositing a metal layer directly" or "direct plating" onto the polymer film refers to forming and building a metal layer on the polymer film using an electrolytic plating process without first using an electroless plating or physical vapor deposition or chemical vapor deposition process to form an initial metal layer on the polymer film. The elimination of this seed layer from the process makes direct metallization faster and less costly than traditional methods in the manufacture of copper clad laminates.

[0075] Energy Storage Devices In one embodiment, the current collector having a polymer film and a first and second metal layer attached to the polymer film can be used in energy storage devices such as lithium ion batteries, capacitors, supercapacitors, fuel cells, and redox flow batteries. Any energy storage device in which the electrical conductivity of the current collector may be useful to complete a circuit and provide power to an external device can benefit from the use of a current collector having a polymer film and a metal layer attached to the polymer film. For example, a lithium ion cell includes a positive electrode (cathode), a negative electrode (anode), and a separator, at least one of which, and preferably all of which, are in ionically conductive contact with an electrolyte solvent.

[0076] In one embodiment, the electrolyte solvent can be combined with one or more electrolytes that provide ions to the electrolyte, making it ionically conductive. Suitable electrolytes include low molecular weight lithium salts and ionic polymers (known as ionomers). Suitable low molecular weight lithium salts include both organic and inorganic salts, such as LiPF6, LiBF4, LiClO4, LiAsF6, LiN(SO2CF3)2, LiN(SO2CF2CF3)2, LiC(SO2CF3)3, among others. The molar concentration of lithium ions in the electrolyte solution can range from 0.1 to 4.0 M, preferably 0.5 to 2.0 M. When the ionic species is an ionomer, it may be desirable to add an amount of low molecular weight lithium salt to the electrolyte solvent to give a concentration in the range of 0.01 to 1.0 M.

[0077] In one embodiment, the electrolyte solvents include primarily acyclic and cyclic organic carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethylene carbonate (EC), and fluorinated ethylene carbonate (FEC); trimethyl phosphate (TMP), tris(2,2,2-trifluoroethyl) phosphate (TFP), tris(2,2,2-trifluoroethyl) phosphatase (TMP), tris(2,2,2-trifluoroethyl) phosphatase (TFP ... Examples of suitable electrolyte solvents include phosphorus-containing compounds such as bis(2,2,2-trifluoroethyl)methylphosphonate (TTFPi), bis(2,2,2-trifluoroethyl)methylphosphonate (TFMP), (ethoxy)pentafluorocyclotriphosphazene (PFPN), and (phenoxy)pentafluorocyclotriphosphazene (FPPN); and monoesters such as methyl acetate (MA), ethyl acetate (EA), methyl formate (MF), methyl propionate (MP), ethyl propionate (EP), and γ-butyrolactone (GBL). In most cases, these electrolyte solvents are used in combinations that include a cyclic organic carbonate (usually EC or PC) and an acyclic carbonate (usually DMC, DEC, or EMC). These combinations have been found in practice to provide an excellent combination of desirable properties such as high ionic conductivity over a wide temperature range and relatively low volatility while at the same time providing excellent life and performance for lithium-ion batteries.

[0078] In one embodiment, the cathode comprises a cathode active material such as a lithium-containing transition metal oxide or phosphate capable of absorbing and releasing lithium ions to a capacity of more than 100 mAh / g, for example, LiCoO2, LiNiO2, Li(Ni,Co)O2, Li(Ni,Co,Mn)O2, LiMn2O4, LiV3O8, Li(Ni,Mn)O4, LiFePO4, LiMnPO4, LiCoPO4, and LiVPO4F. In another embodiment, the cathode active material is Li / Li + The material may exhibit a capacity of greater than 30 mAh / g at a potential range of greater than 4.6 V vs. the reference electrode. In another embodiment, the electrochemical cell is a Li / Li +The cathode is charged to a potential of 4.00 V, 4.10 V, 4.20 V, 4.30 V, 4.35 V, 4.40 V, 4.45 V, 4.5 V, 4.55 V or more, or more than 4.6 V, relative to a reference electrode. One example of such a cathode active material is a stabilized manganese cathode that includes a lithium-containing manganese composite oxide having a spinel structure as a cathode active material. Patent Document 1 discloses a wide range of cathode active materials, which is incorporated herein by reference.

[0079] The cathode active material can be prepared using methods such as the hydroxide precursor method described by, for example, Wang et al., "Electrochemical Properties of Electrochemically Active Materials," vol. 14, no. 1, pp. 1111-1115, 2003. In this method, hydroxide precursors are precipitated from a solution containing the required amounts of acetates of manganese, nickel, and other desired metals by the addition of KOH. The resulting precipitate is oven dried and then reacted with the required amount of LiOH·H2O in oxygen at about 800-950°C for 3-24 hours. Alternatively, the cathode active material can be prepared using a solid-state reaction process or a sol-gel process as described in, for example, Wang et al., "Electrochemical Properties of Electrochemically Active Materials," vol. 14, no. 1, pp. 1111-1115, 2003 ... In a further embodiment, the cathode active material is a sol-gel process comprising a sol-gel process for preparing a cathode active material. The cathode active material can be prepared by mixing an effective amount of the cathode active material (e.g., about 70%-97% by weight), a polymeric binder such as polyvinylidene fluoride, and conductive carbon in a suitable solvent such as N-methylpyrrolidone to form a paste, which is then coated onto a current collector and dried to form the cathode.

[0080] In one embodiment, the anode comprises an anode active material capable of storing and releasing lithium ions. Examples of suitable anode active materials include silicon, lithium metal, lithium alloys (such as lithium-aluminum alloys, lithium-lead alloys, lithium-silicon alloys, and lithium-tin alloys); carbon materials (such as graphite and mesocarbon microbeads (MCMB)); phosphorus-containing materials (such as black phosphorus, MnP4, CoP3); metal oxides (such as SnO2, SnO, TiO2); nanocomposites containing antimony or tin (e.g., antimony-containing nanocomposites); oxides of aluminum, titanium, or molybdenum, carbon, and lithium titanate. In one embodiment, the anode active material is lithium titanate, graphite, lithium alloys, silicon, and combinations thereof. In another embodiment, the anode is graphite. In one embodiment, the graphite-based active material is MCMB (available from Osaka Gas Chemical Co., Ltd., Japan) or carbon fiber (Melblon milled carbon fiber, available from Petoca Materials, Ltd., Japan), both of which can achieve reversible capacities of over 280 mAh / g for lithium insertion. Other suitable carbon-based active materials for the anode include graphite flakes, polycrystalline graphite (PCG), petroleum coke, hard carbon, and natural graphite.

[0081] The anode, including the anode active material, can be fabricated by methods similar to those described above for the cathode, such as dissolving or dispersing a binder, such as a vinylidene fluoride-based copolymer or styrene butadiene rubber, in an organic solvent or water, which is then mixed with a conductive active material to obtain a paste. The paste is then coated onto a current collector. The paste is dried, preferably by heat, so that the active material is bonded to the current collector. Suitable anode active materials and anodes are commercially available from companies such as Hitachi NEI Inc. (Somerset, NJ) and Farasis Energy Inc. (Hayward, CA).

[0082] In one embodiment, the lithium ion battery also includes a porous separator between the anode and the cathode. The porous separator functions to prevent short circuits between the anode and the cathode. The porous separator typically consists of a single or multiple layered sheet of a microporous polymer, such as polyethylene, polypropylene, polyamide, polyimide, or a combination thereof. The pore size of the porous separator is large enough to transport ions to allow ionically conductive contact between the anode and the cathode, but small enough to prevent direct contact between the anode and the cathode or contact through particle penetration or the formation of dendrites. Examples of porous separators suitable for use herein are disclosed in U.S. Patent No. 5,399,992, which is incorporated herein by reference.

[0083] The housing of the lithium ion battery can be any container suitable for containing the lithium ion battery components described above. Such containers can be manufactured in the shape of coin cells, small or large cylindrical or prismatic cases, or pouches.

[0084] In one embodiment, energy storage devices such as lithium ion batteries can be used for grid storage or as a power source for various electronic devices (such as computers, cameras, radios, or power tools), various telecommunications devices, or various transportation equipment (such as cars, trucks, buses, or airplanes). Various cell configurations such as pouch cells, prismatic cells, coin cells, cylindrical cells, wound prismatic cells, wound pouch cells, etc. can be utilized for various battery applications.

[0085] The advantageous properties of this invention can be seen by reference to the following examples, which illustrate, but do not limit, the invention. All parts and percentages are by weight unless otherwise specified. EXAMPLES

[0086] Test Method particle size The particle size of the filler particles in the slurry was measured by laser diffraction using a particle size analyzer (Mastersizer 3000, Malvern Instruments, Inc., Westborough, Mass.) DMAc was used as the dispersion medium.

[0087] surface resistivity To measure surface resistivity according to ASTM D257, a Loresta AX MCPT370 equipped with a PSP Linear 4-point probe (Mitsubishi Chemical Analytech Co., Ltd., Kanagawa, Japan) was used to measure surface resistivity at 15 locations evenly spread across an approximately 12 inch by 12 inch piece of polymer film. The 15 measurements were averaged to determine the surface resistivity of the film. Surface resistivity can be measured on either side of the polymer film.

[0088] Battery Rating The battery performance in the half-cell configuration was evaluated using a battery test system (CT3002A, Landt Instruments, Vestal, NY). All measurements were performed at 25°C. Charge and discharge were performed at 1000 mAh. + / Li 0 The charge / discharge cycles were performed at 2 V to 0.002 V vs. C. The cells were activated at 0.05 C for one cycle before cycling at constant current conditions. In all cases, the charge rate for cell evaluation was 0.1 C. The discharge rate was varied from 0.1 C to 5 C for each subsequent cycle. The C-rate was based on the capacity of the graphite electrodes in the cells. The mid-discharge voltage during the charge / discharge cycles is the voltage of the cell at which half the charge capacity of the electrodes is depleted at a given current or C-rate.

[0089] Carbon Black Slurry For some embodiments, a carbon black slurry was prepared consisting of 9.5 wt.% carbon black powder (Conductex® 7055U, Aditya Birla Group, Marietta, GA), 17.25 wt.% polyamic acid (13.06 wt.% PMDA / ODA and 4.19 wt.% PMDA / BPDA / / ODA / PPD), and 73.25 wt.% DMAc to obtain the conductive filler. Milling and high shear mixing were used to completely and uniformly disperse the particles in the slurry. The median particle size of the filler particles, d 50 (sphere equivalent diameter based on median volume distribution of particles) was less than 1 μm.

[0090] Multilayer Polymer Film Polyamic acid solutions for producing the core and outer layers were prepared separately by chemical reaction between appropriate molar equivalents of monomers in dimethylacetamide (DMAc) solvent. Typically, the diamine dissolved in DMAc was stirred under nitrogen and the dianhydride was added as a solid over a period of several minutes. Stirring was continued to obtain maximum viscosity of the polyamic acid. In some embodiments, 15-60 wt. % carbon black slurry was added to the polyamic acid solution and mixed using a high shear mixer. The composition of the cured film was calculated from the composition of the components in the mixture, excluding the DMAc solvent (which is removed during curing), and taking into account the removal of water during the conversion of the polyamic acid to a polyimide. The viscosity was adjusted by controlling the amount of dianhydride in the polyamic acid composition.

[0091] Multilayer films were cast by coextrusion. Three independent polyamic polymer streams were extruded simultaneously through a multi-cavity die onto a heated moving belt to form a coextruded three-layer polyimide film. The thickness of the polyimide core layer and the top and bottom thermoplastic polyimide outer layers was adjusted by varying the amount of polyamic acid fed to the extruder.

[0092] The extruded multilayer film was dried at an oven temperature ranging from about 95 to about 150° C. The free-standing film was peeled off from the belt and heated with a radiant heater in a tenter oven at a temperature (radiant heater surface temperature) of about 110 to about 805° C. to completely dry and imidize the polymer.

[0093] Examples 1 and 3 In Examples 1 and 3 (E1 and E3), the polymer composition of the core layer included a polyimide derived from a molar ratio of dianhydride to diamine of about 1:1, where the dianhydride was PMDA and the diamine was ODA. The thermoplastic outer layer also included a polyimide derived from a molar ratio of dianhydride to diamine of about 1:1. The dianhydride composition included the monomers PMDA and ODPA in a molar ratio of 20:80, and the diamine composition was 100 mole % RODA monomer. The flow rate of the polyamic acid solution was adjusted to obtain a three-layer film with thermoplastic outer layers each about 6 μm thick and a core layer about 38 μm thick.

[0094] Example 2 In Example 2 (E2), the polymer composition of the core layer included a polyimide derived from a molar ratio of dianhydride to diamine of about 1:1. The dianhydride composition included monomers BPDA / PMDA in a molar ratio of 88:12, and the diamine composition included monomers PPD / ODA in a molar ratio of 95:5. The thermoplastic outer layer also included a polyimide derived from a molar ratio of dianhydride to diamine of about 1:1. The dianhydride composition included monomers PMDA and ODPA in a molar ratio of 20:80, and the diamine composition was 100 mol % RODA monomer. The flow rate of the polyamic acid solution was adjusted to obtain a three-layer film with thermoplastic outer layers each about 6 μm thick and a core layer about 38 μm thick.

[0095] Comparative Example 1 In Comparative Example 1 (E1), the polymer composition of the core layer included a polyimide derived from a molar ratio of dianhydride to diamine of about 1:1. The dianhydride composition included monomers BPDA / PMDA in a molar ratio of 88:12, and the diamine composition included monomers PPD / ODA in a molar ratio of 95:5. The thermoplastic outer layer also included a polyimide derived from a molar ratio of dianhydride to diamine of about 1:1. The dianhydride composition included monomers PMDA and ODPA in a molar ratio of 20:80, and the diamine composition was 100 mol % RODA monomer. The flow rate of the polyamic acid solution was adjusted to obtain a three-layer film with thermoplastic outer layers each about 6 μm thick and a core layer about 38 μm thick.

[0096] [Table 1]

[0097] Films E1-E3 contained carbon black slurry (at the appropriate loading to obtain the target surface resistivity). Film CE1 did not contain conductive filler in any of the layers.

[0098] Films E1-E3 and CE1 were metallized with copper to form a metal layer on the polymer film and tested as current collectors in a half-cell battery configuration. Prior to metallization, film samples were cut to approximately 5 x 7 inches in size and clipped to a stainless steel frame. The film surface was cleaned using a two-step plasma process. Cleaning consisted of exposure to a 300 mTorr plasma using a N2 / CF4 / O2 mixture for 5 minutes, followed by exposure to O2 plasma for 30 seconds. After plasma treatment, the films were immersed in a 1 M aqueous NaOH solution at 45°C with gentle agitation for 90 seconds, then rinsed with running tap water for 2 minutes and directly immersed in an electrolytic plating bath as described below.

[0099] CE1 was prepared by first exposing it to the plasma process described above and a 1M NaOH bath. The sample was then plated using the CIRCUPOSIT™ 6500 electroless copper deposition process without the use of a desmear step and processed as follows: 1. The film was immersed in CIRCUPOSIT™ 6520A Pre-Dip (DuPont de Nemours, Inc., Wilmington, Del.) at pH 2 for 30 seconds with gentle agitation at room temperature. 2. The film is then coated with 200 ppm Pd at 50°C with gentle agitation. 2+ The samples were immersed in CIRCUPOSIT™ 6530 catalyst (DuPont) made up to ionic strength for 60 seconds. 3. The film was then rinsed under running tap water for 60 seconds. 4. The film was then immersed in CIRCUPOSIT™ 6540 reducing agent solution (DuPont) at 32° C. for 60 seconds with gentle agitation. 5. The film was then rinsed under running tap water for 60 seconds. 6. The film was then immersed in a CIRCUPOSIT™ 6550 electroless copper plating bath (DuPont) at approximately 34° C. for 2.5 minutes. 7. The film was then rinsed under running tap water for 60 seconds.

[0100] After electroless plating, the films were dried and stored in a desiccator before being used for electroplating.

[0101] The electroless plating process forms a copper layer of about 80-120 nm on the polyimide film. Then, the electroless plating process is followed by the electrolytic plating process. In CE1, the electroless plated samples were pre-cleaned before the electrolytic bath as follows: 1. The film was pretreated with RONACLEAN™ LP-200 cleaner (DuPont) at 40° C. for 120 seconds. 2. The film was then rinsed with deionized (DI) water for 120 seconds. 3. The film was then treated with 40 g / L sulfuric acid for 30 seconds before being transferred to an electrolytic plating bath. In all examples, sequential electrolytic plating was performed using the MICROFILL™ EVF-II process.

[0102] A copper electroplating bath was prepared by combining 200 g / L copper as copper sulfate pentahydrate, 100 g / L sulfuric acid, 60 ppm chloride ion, 1.25 ml / L MICROFILL™ EVF-II XB, 33 ml / L MICROFILL™ EVF-II XL, and 10 ml / L MICROFILL™ EVF-II XC (all DuPont). The films were electroplated in a 5.5 L plating cell with air agitation set at 2 LPM. Temperature was controlled at 75° F. (24° C.) with a water bath. The films were removed from the desiccator and mounted between two 5″×7″ stainless steel frames with 4.5″×5.5″ windows and treated as follows: 1. The film was plated in a bright acid copper bath at a current density of 5 ASF to a target thickness of 1 μm. 2. After electrolytic copper plating, the film was rinsed with deionized water for 120 seconds, removed from the frame, immersed in ANTITARNISH™ 7130 (DuPont) for 15 seconds, rinsed with deionized water for 30 seconds, and dried in air.

[0103] To prepare the half-cell battery, graphite electrodes were prepared by using a doctor blade to coat a graphite slurry onto the current collector in contact with the film layer. The graphite slurry was prepared from battery grade graphite powder, Super P carbon black (Imerys S.A., France), and styrene butadiene rubber (SBR) binder in a weight ratio of 95.7:1.5:2.8 (graphite:Super P carbon:SBR binder) to form a 46 wt% solids slurry in water and mixed with a magnetic stirrer for approximately 24 h. After coating the current collector, the assembly was dried in a convection oven at 70 °C for at least 24 h before use. The loading of graphite active component on the electrode was 5 mg (total solids) / cm. 2 , or 5*0.957=4.785g graphite / cm 2 A 3 / 8 inch circle was punched out of the electrode for cell evaluation. A 0.25 mm (10 mil) thick lithium metal foil (Aldrich, Milwaukee, WI) was used as the counter electrode for the half-cell measurements. Similar to the graphite electrode, a 3 / 8 inch circle was used.

[0104] Half-cell batteries were made in the form of coin cells and assembled using Celgard® separator 2325 (Celgard, LLC. Charlotte, NC), a lithium foil counter electrode (0.25 mm thick), a graphite electrode, and a few drops of non-aqueous electrolyte composition obtained from Aldrich (1 M LiPF6EC / EMC / DMC, 1:1:1 by volume). The lithium foil counter electrode, graphite electrode, separator, and anode were stacked and sandwiched into a 2032 stainless steel coin cell can (MTI, California) to form a half cell in an argon-filled dry box. For testing, all C-rates were calculated based on an assumed charge capacity of 300 mAh / g. Thus, each coin cell battery had an assumed capacity of 1.44 mAh. All measurements were performed at 25°C. The cells were cycled at a charge rate of 0.1C, followed by increasing discharge rates from 0.1C to 0.2C, 1C, 2C, and 5C in subsequent cycles.

[0105] For each discharge cycle, the mid-discharge voltage (the voltage at which the cell reaches half its charge capacity during discharge) was determined from the discharge curve. This was used to characterize the cell polarization related to the cell's internal resistance. Two to three coin cells were fabricated from each current collector. The average mid-discharge voltages of the current collectors at 2C and 5C are shown in Table 1. For CE2, 9 μm battery-grade copper foil (>99.95% purity, resistivity 0.168 Ω g / m 2 , surface roughness less than 0.4μm, tensile strength 41kg / m 2 ) was used as the current collector in the same half-cell configuration as used in the other examples.

[0106] [Table 2]

Claims

1. 1. A current collector comprising a polymer film, a first metal layer adhered to the polymer film, and a second metal layer adhered to the polymer film opposite the first metal layer, the polymer film comprises a conductive filler and has a surface resistivity of 1 megaohm / square or less; the first and second metal layers each have a thickness of 3 μm or less; A current collector having at least 20% lower mid-discharge voltage when compared to untreated battery grade copper foil, based on standard lithium ion battery half-cell testing at a temperature of 25° C. and a discharge rate of 2C or higher.

2. The current collector of claim 1 , wherein the polymer film comprises an imide group-containing polymer.

3. The polymer film is a first outer layer comprising a first polymer; a second outer layer comprising a second polymer; 10. The current collector of claim 1, comprising a multilayer film comprising a core layer comprising a third polymer, said core layer being between said first and second outer layers, and said conductive filler being present in one or more of said layers.

4. 4. The current collector of claim 3, wherein one or more of the first, second, and third polymers comprises an imide group-containing polymer.

5. 10. The current collector of claim 1, wherein the conductive filler is present in the polymer film at a concentration in the range of 5 to 65 weight percent, based on the total weight of the polymer film.

6. 13. An energy storage device comprising the current collector of claim 1.

7. 7. The energy storage device of claim 6, wherein the energy storage device is selected from the group consisting of a lithium ion battery, a capacitor, a supercapacitor, a fuel cell, and a redox flow battery.

Citation Information

Patent Citations

  • Nonaqueous electrolyte compositions

    US20160087307A1

  • Positive electrode active material for lithium battery

    US5738957A

  • Polyimide nanoweb with amidized surface and method for preparing

    US8518525B2